2022
DOI: 10.3389/fonc.2022.919118
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome analysis reveals the genomic complexity in metastatic cutaneous squamous cell carcinoma

Abstract: Metastatic cutaneous squamous cell carcinoma (CSCC) is a highly morbid disease requiring radical surgery and adjuvant therapy, which is associated with a poor prognosis. Yet, compared to other advanced malignancies, relatively little is known of the genomic landscape of metastatic CSCC. We have previously reported the mutational signatures and mutational patterns of CCCTC-binding factor (CTCF) regions in metastatic CSCC. However, many other genomic components (indel signatures, non-coding drivers, and structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 93 publications
2
15
0
Order By: Relevance
“…The absence of HOXA9 positively regulates HIF-1 and its downstream glycolytic regulators, which enhances glycolysis necessary for cSCC development, proliferation, migration, and invasion [ 15 ]. Using whole-genome sequencing, Thind et al demonstrated significant recurrent copy number loss in the tumor suppressor genes KANSL1 and PTPRD [ 16 ]. Likewise, KMT2C , CREBBP , and NCOA2 were identified to demonstrate tumor-suppressive roles in the initiation and progression of human cSCC [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of HOXA9 positively regulates HIF-1 and its downstream glycolytic regulators, which enhances glycolysis necessary for cSCC development, proliferation, migration, and invasion [ 15 ]. Using whole-genome sequencing, Thind et al demonstrated significant recurrent copy number loss in the tumor suppressor genes KANSL1 and PTPRD [ 16 ]. Likewise, KMT2C , CREBBP , and NCOA2 were identified to demonstrate tumor-suppressive roles in the initiation and progression of human cSCC [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thind et al also observed that the 3′ UTR regions of EVC (48%), PPP1R1A (48%), and LUM (16%) were significantly functionally altered (Q-value < 0.05) in the non-coding genome of cSCC. Moreover, significant recurrent copy number gains in CALR , CCND1 , and FGF3 were observed for coding regions [ 16 ]. In a recent study by Yan et al, differential expression analysis demonstrated that many members belonging to the S100 gene family, the SPRR gene family, and FABP5 were significantly upregulated in cSCC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer rates in organ transplant recipients are generally higher, and this rate is between 60–100 times greater than the age-matched population for cSCC. The extremely high tumour mutational burden seen in whole genomic analysis of metastatic cSCC [ 101 ] underpins the predilection for disease progression in those patients with impaired immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…HNcSCC is biologically distinct from mucosal HN SCC, with different aetiological factors, demographics, and genetics. Metastatic HNcSCC is the most highly mutated human cancer due to life-long exposure to ultraviolet (UV) radiation, with tumour mutation burdens several folds higher than HN mucosal SCC [ 45 , 46 , 47 , 48 ]. Furthermore, regional metastases from HNcSCC are usually metachronous from the primary tumour and in many cases (20–30%), the primary or index lesion cannot be identified.…”
Section: Discussionmentioning
confidence: 99%